PENGATURAN PENERBITAN OBLIGASI OLEH PEMERINTAH DAERAH - Endang Retnowati (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
One of local revenue source is obtained from local loan. UU No. 33/2004 about Financial Balancing of Central dan Local Goverment makes enable for local government to get public loan by issuing financial bond. Since this is something new in Indonesia, a regulation and law protection for investor should be set up. The two existing regulations, stock exchange regulation and UU No. 33/2004 are likely have some disputed things concerning term of loan the type and purpose of loan and collateral.